PREPARATION OF TEMPERATURE-RESPONSIVE POLYMER BY GRAFTING OF N-ISOPROPYLACRYLAMIDE (NIPAAM) ONTO SOLID WASTE CASSAVA - Irwan Ginting Suka; Wasinton Simanjuntak (Universitas Gadjah Mada, 2011)
In this study, cellulose prepared from solid waste of cassava industry was functionalized with N-isopropylacrylamide (NIPAAm) using grafting technique with the aid of cerium (IV) as initiator, to obtain temperature responsive polymer. In this research, several factors influencing the grafting process and the characteristics of the grafted polymer were investigated, including concentration of monomer and initiator, temperature, reaction time, and solvent used. The functionality of native and grafted cellulose was analyzed using FTIR spectroscopic technique and the response of grafted polymer toward temperature was evaluated with water absorption experiment. Increased concentration of both monomer and initiator was found to promote percentage of polymerization, and utilization of organic solvent was found to enhance the percentage of polymerization. From absorption experiment, it was found that the produced polymer was responsive toward temperature of its environment, as indicated by higher water adsorption at temperature of 5 °C compared to that adsorbed at temperature of 50 °C.